THE GENE OF ALPHA2A-ADRENORECEPTOR AND ESSENTIAL ARTERIAL HYPERTENSION - T. A. Bairova; V. V. Dolgikh; L. I. Kolesnikova; A. S. Kosovtseva; L. F. Sholokhov (Российский кардиологический журнал)
Aim. To study the importance of -1291C>G gene polymorphism of α -2А adrenoreceptor in the arterial hypertension development in male adolescents.Material and methods. Totally 207 adolescents included, of those 110 males with verified essential hypertension at the age of 14 to 17 (15,92±1,12) of slavic ethnicity. The control group consisted of 97 same by the age, gender and ethnicity almost healthy adolescents.The investigation program included clinical and anamnestic data, laboratory study with blood katecholamines, blood pressure monitoring, echocardiography and genotyping. The specimen for genomic test was total DNA. It was extracted from lymphocytes of peripheral blood with the “DNAsorb-V” equipment of FSSI CSRIE Rospotrebnadzor according to the manual. Genotyping was done by PDF-study by commercial equipment of FSPI GosSRIgenetics. The final detection was done on the “Gel-Doc 2000” equipment (Bio-Rad).Results. The occurence of G-allele in populational cohort and among EAH did not differ (controls 0,242±0,030; among patients — 0,204±0,027, р=0,326). In G-allele carriers of -1291C>G polymorphism of α -adrenoreceptor gene the 2А hyperdiastolic variant of vegetative supply dominates, and significantly higher thelevels of common and mean peripheral resistance, that are combined with compensatory decrease of inotropic values (efflux volume, cardiac index, cardiac output). There were no significant differences of plasma katecholamines, including norepinephrine, in patients various genes carriers.Conclusion. G-allele carriers of -1291C>G polymorphism of α -adrenoreceptor2А gene ADRA2A should be marked as risky alleles for the risk of essential arterialhypertension in male europeoid adolescents.